Testing Asymmetrical Effect of Exchange Rate on Saudi Service Sector Trade: A Non-Linear ARDL Approach - Mahmood, Haider; Al-Khateeb, Tarek Yousaf Tawfik (International Journal of Economics and Financial Issues, 2017)
Present study explores the impact of devaluation and appreciation (negative and positive movements of exchange rate) on services sector trade by applying Non Linear ARDL technique of Shin et al. (2014). This study confirms asymmetrical effects in case of all sectors in short run and long run effects may improve the trade balance of all sectors. Overall devaluation confirms existence of J-curve after some lag. This study also found that appreciation of a Saudi currency may put up adverse effects on trade balance in all services sectors except travel, construction and tourism sectors. The increase in world income may support to enhance exports of Saudi Arabia, while rise in Saudi Arabia’s income may have negative effects on trade balance of all services sectors except travel and tourism. Keywords: Devaluation, Trade, Asymmetry JEL Classifications: F31, F14, D82